Program Pelatihan Digitalisasi Media Literasi Untuk Pendidikan Bahasa dan Sastra di Kota Tegal Jawa Tengah - Noeris Meiristiani; Ihda Rosdiana; Anin Eka Sulistyawati; Sanday Jamaludin; Yuvita Yuvita (Asosiasi Dosen Pengabdian kepada Masyarakat Indonesia, 2022)
The literacy activities of Tegal Municipality society show significant development where the government pays attention to the people by providing literacy facilities and programs. The people are also active in producing literary works and texts that can be used for language learning. On the other hand, advances in digital technology have not been widely utilized for the development of this potential. Therefore, UPS Tegal collaborates with Poddium to develop the digitalization of literacy media for language and literature education to create an Independent Learning-Independent Campus ecosystem. The purpose of transforming people's works from text to audio format is that these works can reach wider audience to improve the people's literacy. This program involved 17 lecturers, 70 students, and 2 literacy communities. Students are given trainings of script selection, audiobook and podcast production, and product distribution. Then, students are supervised to produce 20 audiobooks and 50 podcasts which are then uploaded to the Poddium's application. The target beneficiaries of this product can access the application for free for the first 6 months, namely students, schools, libraries, and people in general. This program was supported by the government through Matching Fund of Kedaireka from the Directorate General of Higher Education in 2021.